To solve the equation 3x + 5 = -2x + 15, we need to isolate the variable x.
First, let's combine like terms on both sides of the equation. Add 2x to both sides:
3x + 2x + 5 = -2x + 2x + 15
Simplifying:
5x + 5 = 15
Next, subtract 5 from both sides of the equation:
5x + 5 - 5 = 15 - 5
Simplifying:
5x = 10
Now, divide both sides of the equation by 5 to solve for x:
(5x) / 5 = 10 / 5
Simplifying:
x = 2
Therefore, the solution to the equation 3x + 5 = -2x + 15 is x = 2.
Solve the equation:
`3x+5=-2x+15`
1 answer